A business model optimization study of Macao’s urban space and historic districts - Gengrui Li (Journal of Asian Architecture and Building Engineering)
This article takes Macao’s urban space and historical districts as the research object, aiming to explore how to balance commercial interests and prosperity with cultural protection. The Business Model Canvas (BMC) model is used to analyze the various components of the existing business model. A questionnaire survey and linear regression analysis method are adopted to explore the key factors affecting the development of the block’s business model, identify and solve the development imbalance caused by the single business model and insufficient cultural protection. The results show that the statistical test P-values of 18 independent variables and constant terms are all less than 0.05, and they can be included in the final regression model. The proportion of tourists, residents, participation rate in cultural activities, and utilization rate of leisure facilities have a significant positive impact on the level of business model development. However, factors such as rental income, crowd density, social media interaction, and cultural heritage quantity have a negative impact. This article provides a new perspective on urban planning and business model optimization in Macao. By drawing on Macao’s successful experience, other cities can promote sustainable economic development and harmonious coexistence while protecting historical and cultural heritage.